2018
DOI: 10.1186/s41983-018-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arteriovenous malformations in the era of embolization for angiographic cure: a single-center experience in Egypt

Abstract: BackgroundEmbolization for cerebral arteriovenous malformations (AVMs) has evolved in the last decade with evolution in both equipment and material. Embolization targets have expanded to include angiographic cure.MethodsTo discuss the technical and management outcomes of our first cerebral AVM case series treated with embolization. The clinical, angiographic, treatment, and outcome variables of consecutive cerebral arteriovenous malformation cases, treated with curative embolization, between January 2011 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Mohram et al (15) reported that modified Rankin Scale (mRS) ranged from 0 to 4, 9 patients (36.0%) had grade 0, 8 patients (32.0%) had grade 1, 4 patients (16.0%) had grade 2, 3 patients (12.0%) had grade 3 and one patient (4.0%) had grade 4. While Elewa (10) reported that regarding modified Rankin Scale, 16 patients (76.2%) were at grade 1, 4 patients (19.0%) were at grade 2, and 1 patient (4.8%) was at grade 3.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mohram et al (15) reported that modified Rankin Scale (mRS) ranged from 0 to 4, 9 patients (36.0%) had grade 0, 8 patients (32.0%) had grade 1, 4 patients (16.0%) had grade 2, 3 patients (12.0%) had grade 3 and one patient (4.0%) had grade 4. While Elewa (10) reported that regarding modified Rankin Scale, 16 patients (76.2%) were at grade 1, 4 patients (19.0%) were at grade 2, and 1 patient (4.8%) was at grade 3.…”
Section: Discussionmentioning
confidence: 98%
“…According to meta-analyses of extensive AVM case series, up to 7.4% of patients having microsurgery for AVM excision may experience serious side effects (9) . Endovascular embolization could serve as a curative option for AVM treatment with accepted morbidity and mortality (10) . Procedural safety was evaluated by assessing the periprocedural complications occurring within 1 month after embolization.…”
Section: Discussionmentioning
confidence: 99%
“…In our case series, we found an occlusion rate according to what has been reported. In this study, we assessed the obliteration rate immediately after the embolization; however, NBCA has shown a higher cure rate over time, which we were unable to assess [25].…”
Section: Discussionmentioning
confidence: 99%